Total Barley Maiya Alkaloids Prevent Increased Prolactin Levels Caused by Antipsychotic Drugs and Reduce Dopamine Receptor D2 via Epigenetic Mechanisms - Cao, Yu-Ling; -Zhu, Li; Zhang, Hong; Meng, Jun-Hua; Wu, Hua-Jun; Wang, Xiong; Wu, Jin-Hu; Zou, Ji-Li; Fang, Mao-Sheng; An, Jing; Chen, Yong-Gang (Frontiers in Pharmacology, 2022)
Aims: The dopamine D2 receptor (DRD2) plays an important role in the increased prolactin (PRL) levels associated with the pathogenesis of antipsychotic drugs (ADs). Maiya has been used to treat diseases associated with high PRL levels. Epigenetic mechanisms can be related to DRD2 expression. We investigated the role of DRD2 methylation in the induction of PRL expression by ADs and the mechanism underlying the effects of total barley maiya alkaloids (TBMA) on this induction. Methods: The methylation rate of DRD2 in 46 people with schizophrenia who took risperidone was detected by MassARRAY sequencing. A rat model of risperidone-induced PRL was established, and the potential protective effects of TBMA and its components (e.g., hordenine [Hor]) on these increased PRL levels were investigated. The PRL concentration was detected by ELISA. PRL, DRD2, DNA methyltransferase (DNMT1, DNMT3α, and DNMT3β) protein and mRNA expression were detected by western blotting and real-time polymerase chain reaction (RT-PCR), respectively. The positive rate of methylation in the DRD2 promoter region of rats was detected by MassARRAY sequencing. Results: Clinical studies showed that the positive rate of DRD2 methylation associated with increased PRL levels induced by ADs was significantly higher than in the normal prolactinemia (NPRL) group. In vivo and vitro, TBMA and Hor inhibited this induction of PRL expression and increased DRD2 expression by inhibiting the expression of the DNMTs. Conclusions: TBMA and hordenine increased DRD2 expression by inhibiting DNMT-dependent DRD2 methylation.